Tensor description of X-ray magnetic dichroism at the Fe L2,3-edges of Fe3O4 - Elnaggar, Hebatalla; Haverkort, Maurits W.; Hamed, M. H.; Dhesi, S. S.; de Groot, F. M. F. (Journal of synchrotron radiation, 2021)
A general description of magnetic dichroism effects in X-ray absorption spectroscopy using a few fundamental spectra extracted from experimental measurements is provided. The accuracy of the procedure is investigated theoretically.
Im Text sind "2,3", "3" und "4" tiefgestellt, "L" kursiv geschrieben
Gesehen am 10.04.2022